THE FIFTH SEMESTER STUDENTS’ SENTENCE VARIETIES IN WRITING STORIES AT UIN ALAUDDIN MAKASSAR - Nur, Nur Aliyah; Hilmia, Sofiya; Muthi'ah, Muthi'ah; Abubakar, Multazam (English Language, Linguistics, and Culture International Journal, 2021)
The study aims to describe the students’ ability to change the monotonous story to be interesting by using sentence varieties. The researchers used qualitative descriptive method and the subjects were the fifteen fifth semester students of English Education Department at Alauddin State Islamic University of Makassar (UIN Alauddin Makassar), especially PBI 3-4. Writing test and interview guidelines were used as the research instrument in which the students were asked to rewrite the texts based on the texts given to them and their opinion about sentence varieties used in the story. The findings of students’ tests indicated that majority of students used all kind of sentences, while, minority of students used three types sentences in the stories. Two students used all types, except compound sentence in the first story, compound-complex sentence in second story and compound-complex sentence in both of the stories. The findings of students’ interview showed that five students felt that the stories which only contained simple sentence were not interesting, four students felt the stories look bored to read, two students felt the stories were monotonous, two students said the stories not better to read, one student felt the stories too easy to read because like child’s stories and one student said the stories which contained sentence varieties were comfortable to read by the students in university. In conclusion, the data showed majority of students’ used sentence varieties in their stories and majority of students felt boring to read the story which contained simple sentences.